Information sensorium as a framework to read images: an interdisciplinary investigation on “reading images” using the Wayfarer Triptych by Jheronimus Bosch as a case study - Sum, Hedren Wai Yuan (Nanyang Technological University, 2024)
The research aimed to improve our understanding of the hidden meanings and linguistic dialogue between images and texts. It sought to address three main questions: How do scholars read images in paintings over time? How can a digital archive system be designed to guide users to read images online? And how can a knowledge organisation system be designed to present the understanding that scholars have developed? Scholars have noted a need for an integrative framework considering the fluidity of meanings influenced by the intentions and experience of the informational user and the interfaces they interacted with while reading images. Hence, a new framework, Information Sensorium, was formulated through a critical discourse of theories and ideas around the intersecting notions of information, images, and meaning that span information science, art history, and philosophy. Information Sensorium provides an approach to advance the understanding of images of a work of art. Through five facets, the framework shifted from generalising understanding towards evaluating what and how the understanding was achieved and to what degree. Using the paintings of the Wayfarer Triptych by Jheronimus Bosch as a showcase, Information Sensorium was validated for its potential to read images. It also considers how meanings manifest or new understanding can be derived through visualisation and simulation techniques. As a result, a series of digital knowledge interfaces were developed to explore how the facets of Information Sensorium can be translated into interactions of a knowledge interface using various human-computer interaction approaches. In conclusion, this study demonstrated the potential of reading images through an integrative framework, Information Sensorium. It sets the foundation for further developments that interface and aggregate the image-text relationships of different types of images across cultures, periods, and genres to achieve an understanding of worldviews through the human sensorium.